Successive approximation method for Caputo q-fractional IVPs - Salahshour, S.S.; Ahmadian, A.; Chan, C.S. (Elsevier, 2015)
Recently, Abdeljawad and Baleanu (2011) introduced Caputo q-fractional derivatives and used it to solve Caputo q-fractional initial value problem. For this purpose, they applied successive approximation method to obtain an explicit solution; but did not clarify under which conditions that this method will be convergence. In this paper, we propose q-Krasnoselskii-Krein type condition to investigate the convergence of the method. (C) 2014 Elsevier B.V. All rights reserved.